Political Dynamics of Fulfilling Civil Rights of Religious Minority Communities in Cilegon City - Mayrudin, Yeby Ma'asan; Amalinda, Valerie (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
This article focuses on discussing the polemic about the establishment Church in Cilegon which has never been resolved. Minority communities are hampered in realizing religious freedom. They are subjugated by cultural, social and political conditions and groups who firmly oppose the Church's presence in Cilegon. We use descriptive qualitative research methods which are useful for exploring the main problem in a holistic manner. The theory used is freedom and plurality by Hannah Arendt. This research show that the concept of plurality and freedom of worship for non-Muslim communities has not been fully implemented due to pressure from conservative groups. This illustrates that the condition of representation of living together is only limited to drinking coffee with Muslim. But, on the basic understanding that every human being as a unique person is entitled to a freedom. The political dynamics in Cilegon also look very conservative, the political elites have no sensitivity towards minority groups. They are completely reluctant to leave their comfort zone, because the elites in the city do not strive for justice for minorities. The practice of plurality and conditions of freedom of worship have not been fully realized in the current living conditions of Cilegon society.